2001
DOI: 10.1104/pp.125.4.1813
|View full text |Cite
|
Sign up to set email alerts
|

ANT1, an Aromatic and Neutral Amino Acid Transporter in Arabidopsis

Abstract: A new amino acid transporter was identified from the Arabidopsis expressed sequence tag cDNAs by expressing the cDNA in a yeast amino acid transport mutant. Transport analysis of the expressed protein in yeast showed that it transports aromatic and neutral amino acids, as well as arginine. This transporter (ANT1, aromatic and neutral transporter) also transports indole-3-acetic acid and 2,4-dichlorophenoxyacetic acid. The cDNA is 1.6 kb in length with an open reading frame that codes for a protein with 432 ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 32 publications
(30 reference statements)
1
87
3
Order By: Relevance
“…BLAST analysis revealed that the rice Bh4 encoded an amino acid transporter. Phylogenetic comparison of BH4 protein and other amino acid transporters showed that BH4 was closely related to AtANT1, an aromatic and neutral amino acid transporter in Arabidopsis (Arabidopsis thaliana; Chen et al, 2001; Fig. 4A; Supplemental Fig.…”
Section: Bh4 Encodes An Amino Acid Transporter Protein and Is Specifimentioning
confidence: 99%
“…BLAST analysis revealed that the rice Bh4 encoded an amino acid transporter. Phylogenetic comparison of BH4 protein and other amino acid transporters showed that BH4 was closely related to AtANT1, an aromatic and neutral amino acid transporter in Arabidopsis (Arabidopsis thaliana; Chen et al, 2001; Fig. 4A; Supplemental Fig.…”
Section: Bh4 Encodes An Amino Acid Transporter Protein and Is Specifimentioning
confidence: 99%
“…Phylogenetic relationship between the AtProTs and related proteins. The analysis was performed using the aligned protein sequences of the Arabidopsis ATF gene family that, in addition to the ProTs, contains several groups of amino acid permeases (AAPs, LHTs, ANT-like proteins) as well as potential auxin transporters (AUX1; Fischer et al, 1998;Chen et al, 2001;Wipf et al, 2002). Proteins from other plant species were included for the ProT-like and the At1g08230-like proteins.…”
Section: Atprot3 Is a Novel Member Of The Aprot Gene Familymentioning
confidence: 99%
“…The ATF1 superfamily (amino acid transporter family 1) consists of several subfamilies: the AAPs (amino acid permeases), the LHTs (lysine histidine transporters), the ProTs (proline and compatible solutes transporters), the AUXs (putative auxin transporter) and several new subfamilies (25). One transporter, ANT1, of this new subfamily has been characterized recently as a transporter for neutral and aromatic amino acids (26). The CAT subfamily (cationic amino acid transporters) is a member of the second plant amino acid transporter family, namely the APC-superfamily (24,27).…”
mentioning
confidence: 99%